Cardiopulmonary Outcomes After the Nuss Procedure in Pectus Excavatum - Dawn E. Jaroszewski; Juan M. Farina; Michael B. Gotway; Joshua D. Stearns; Michelle A. Peterson; Venkata S. K. K. Pulivarthi; Peter Bostoros; Ahmad S. Abdelrazek; Ashwini Gotimukul; David S. Majdalany; Courtney M. Wheatley‐Guy; Reza Arsanjani (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Pectus excavatum is the most common chest wall deformity. There is still controversy about cardiopulmonary limitations of this disease and benefits of surgical repair. This study evaluates the impact of pectus excavatum on the cardiopulmonary function of adult patients before and after a modified minimally invasive repair. Methods and Results In this retrospective cohort study, an electronic database was used to identify consecutive adult (aged ≥18 years) patients who underwent cardiopulmonary exercise testing before and after primary pectus excavatum repair at Mayo Clinic Arizona from 2011 to 2020. In total, 392 patients underwent preoperative cardiopulmonary exercise testing; abnormal oxygen consumption results were present in 68% of patients. Among them, 130 patients (68% men, mean age, 32.4±10.0 years) had post‐repair evaluations. Post‐repair tests were performed immediately before bar removal with a mean time between repair and post‐repair testing of 3.4±0.7 years (range, 2.5–7.0). A significant improvement in cardiopulmonary outcomes (P<0.001 for all the comparisons) was seen in the post‐repair evaluations, including an increase in maximum, and predicted rate of oxygen consumption, oxygen pulse, oxygen consumption at anaerobic threshold, and maximal ventilation. In a subanalysis of 39 patients who also underwent intraoperative transesophageal echocardiography at repair and at bar removal, a significant increase in right ventricle stroke volume was found (P<0.001). Conclusions Consistent improvements in cardiopulmonary function were seen for pectus excavatum adult patients undergoing surgery. These results strongly support the existence of adverse cardiopulmonary consequences from this disease as well as the benefits of surgical repair.